Solve
\((6p+2q+10)-(p+3q-2)\).
\(\begin{aligned}&\space(6p+2q+10)-(p+3q-2) \\\\&=6p+2q+10-p-3q+2 \\\\&=6p-p+2q-3q+10+2 \\\\&=5p-q+12. \end{aligned}\)
\(\begin{aligned} &\space(h-4k)^3 \\\\&=(h-4k)\times(h-4k)\times(h-4k) \end{aligned}\)
We can see that \(n=3\) means the multiplication is repeated \(3\) times.
Calculate the product of \(-4mn\times7m^2\).
\(\begin{aligned}&\space-4mn\times7m^2 \\\\&=-4\times m\times n\times7\times m\times m \\\\&=-4\times7\times m\times m\times m\times n \\\\&=-28m^3n. \end{aligned}\)
Calculate the quotient of \(36pq\div4q^2\).
\(\begin{aligned}&\space36pq\div4q^2 \\\\&=\dfrac{36pq}{4q^2} \\\\&=\dfrac{36\times p\times q}{4\times q\times q} \\\\&=\dfrac{9p}{q}. \end{aligned}\)
Assess yourself by staged practices